2019
DOI: 10.3390/md17080446
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Two New Sorbicillinoids by Overexpression of the Global Regulator LaeA in a Marine-Derived Fungus Penicillium dipodomyis YJ-11

Abstract: Overexpression of the global regulator LaeA in a marine-derived fungal strain of Penicillium dipodomyis YJ-11 induced obvious morphological changes and metabolic variations. Further chemical investigation of the mutant strain afforded a series of sorbicillinoids including two new ones named 10,11-dihydrobislongiquinolide (1) and 10,11,16,17-tetrahydrobislongiquinolide (2), as well as four known analogues, bislongiquinolide (3), 16,17-dihydrobislongiquinolide (4), sohirnone A (5), and 2′,3′-dihydrosorbicillin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Yu et al [ 150 ] showed that the overexpression of LaeA in the Penicillium dipodomyis marine-derived strain YJ-11 leads not only to morphological but also metabolic changes. Overexpression mutants displayed the ability to produce several sorbicillinoids, two of which are new compounds, as well as four known sorbicillin analogues.…”
Section: Regulation Of Secondary Metabolismmentioning
confidence: 99%
“…Yu et al [ 150 ] showed that the overexpression of LaeA in the Penicillium dipodomyis marine-derived strain YJ-11 leads not only to morphological but also metabolic changes. Overexpression mutants displayed the ability to produce several sorbicillinoids, two of which are new compounds, as well as four known sorbicillin analogues.…”
Section: Regulation Of Secondary Metabolismmentioning
confidence: 99%
“…by Bok and Keller has revolutionized the understanding of fungal secondary metabolism [ 11 ]. The dynamic roles of LaeA have been studied in many aspects of fungal biology, such as in asexual and sexual differentiation, in phenotype changes including pigmentation and sporulation [ 12 , 13 ], reducing [ 14 ] or increasing secondary metabolite production [ 11 , 15 , 16 ], and activation of cryptic gene clusters [ 13 , 17 ]. Numerous studies based on model Aspergillus nidulans LaeA have been carried out during the past several years, which proved its mechanisms ( Figure 1 ) and regulatory role in secondary metabolism [ 11 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we report here nine sorbicillinoid derivatives (1-9), including six new compounds, isolated from the spongederived fungus T. reesei (HN-2016-018). To date, more than 130 sorbicillinoid derivatives have been reported (Meng et al, 2016(Meng et al, , 2018(Meng et al, , 2019Zhang et al, 2018Zhang et al, , 2019Cao et al, 2019;Wang et al, 2019;Yu et al, 2019). In this study, we discovered two novel sorbicillinoids (1-2) with a characteristic naphthalenetrione ring and two rare sorbicillinoids (3-4) possessing a bicycle (3.2.1) lactone skeleton (Figure 6), where only three compounds with such distinctive skeleton have been reported previously.…”
Section: Resultsmentioning
confidence: 49%